Design of non-equiatomic high entropy alloys with heterogeneous lamella structure towards strength-ductility synergy. (September 2018) - Zhang, Cheng; Zhu, Chaoyi; Harrington, Tyler; Vecchio, Kenneth
Abstract: A non-equiatomic FeNiCoAlCrB (NCACB) high entropy alloy (HEA) with a heterogeneous lamella (HL) structure is fabricated through conventional thermomechanical processing. In the HL microstructure, fine-grain regions result from inhibited grain growth due to Zener pinning of boundaries by NiAl (B2) precipitates, while coarse-grained regions originate from grain growth within large deformation bands in the absence of precipitates. A back-stress strengthening mechanism, unique to deformation of heterogeneous microstructures, is verified through mechanical behavior and electron backscatter diffraction enabled geometrically necessary dislocation density analysis. This mechanism gives rise to the combination of both high strength and high ductility in HL-NCACB-HEA. Graphical abstract: Heterogeneous lamella structured high entropy alloy is fabricated through thermal mechanical processing routes to overcome strength-ductility trade-off. Its unique grain structure containing both fine grained (FG) and coarse grained (CG) lamella is illustrated in the EBSD orientation map in the through thickness direction, along with the grain area map showing coarse grained lamella. Exceptional mechanical property is attributed to the back-stress strengthening, which is correlated to the generation of excess geometrically necessary dislocations near the CG-(soft)/FG-(hard) interface to maintain compatibility. Unlabelled Image